Transformasi Dan Inovasi Pelindungan Hukum Pekerja Migran Indonesia Di Sektor Informal - Henry Anderson Parapat; David Banjarnahor (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This study examines the effectiveness of the implementation of Law No. 18 of 2017 in providing legal protection for Indonesian migrant workers in the informal sector, focusing on the pre-placement, placement, and post-placement stages. It also identifies the main obstacles and proposes strategic measures to address them. Employing a normative juridical method with statutory and conceptual approaches, the study analyzes relevant legislation, legal doctrines, and practical applications concerning migrant worker protection. The findings indicate that althought the regulatory framework is normaitvely comprehensive, its implementation remains hampered by weak institutional coordination, limited legal literacy, social stigma, and non-procedural recruitment practices. To address these challenges, the study recommends strengthening cross sectoral collaboration, accelerating the harmonization of implementing regulations, enhancing human resource capacity, and promoting inclusive legal education and services. Throught these integrated strategies, the legal protection for Indonesian migrant workers in the informal sector is expected to become more effective, responsive, and sustainable.